Distance matters in away games: Evidence from the German football league - Harald Oberhofer; Tassilo Philippovich; Hannes Winner (University of Salzburg, Department of Social Sciences and Economics, 2009)
This paper assesses the role of distance in professional team sports, taking the example of football (soccer). We argue that a team's performance in terms of scored and conceded goals decreases with the distance to the foreign playing venue. To test this hypothesis empirically, we investigate 6,389 away games from the German Football Premier League ('Erste Deutsche Bundesliga') between the playing seasons 1986-87 and 2006-07. We find that distance increases a guest team's propensity to concede goals and exhibits a negative but insignificant impact on the ability to score goals. The parameter estimates of the squared distance terms indicate that the effects of distance on team performance are non-monotonic. Further, focusing on the outcome of the game (i.e., win, draw or defeat) as a measure of the overall success of a football team we observe significantly negative effects of distance.
Keywords: L25; L83; C29; 330; Professional team performance; distance; event count data; poisson regression model